A Case Study of Contextual and Emotional Modulation of Source-case Selection in Analogical Arguments - Guarini, Marcello (Informal Logic, 2023)
In making analogical arguments about actions, is more similarity between the source and target cases always better? No: all things considered, more similarity is not always better, even if the similarities are all relevant. The reason is that the context of the argument, including emotional considerations, modulates the selection of the source case to service the goals of the argument. If the goals of the argument include persuasion and even modifying someone’s emotional state, increasing the overall similarity between the source and target may be counterproductive.